1994
DOI: 10.1111/j.1467-6494.1994.tb00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Children Use the Big Five, Too? Content and Structural Form In Personality Description

Abstract: Free personality descriptions generated by 11-year-olds in the Role Construct Repertory Test (Kelly, 1955) were content-analyzed. The children's personality constructs were coded according to structural form (e.g., habits, preferences, traits) and "Big Five" personality content domain (e.g., Agreeableness, Conscientiousness). Findings showed that the children generated constructs from all of the Big Five personality domains. Agreeableness constructs were used most frequently, replicating the prevalence of that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
0
34
2
1
Order By: Relevance
“…For instance, Mervielde (1994) noted that school teachers describing their pupils most often referred to agreeableness and, to a lesser degree, to extraversion and emotional stability. In Donahue's (1994) study, the most popular domain (agreeableness) was used by 73% of the subjects, whereas the least popular domain (emotional stability) was used by only 16%. On the basis of a series of five studies, Smith and Kihlstrom (1987) concluded that individuals use some of the five dimensions some of the time.…”
Section: Interviewers' Assessments Of Personalitymentioning
confidence: 99%
“…For instance, Mervielde (1994) noted that school teachers describing their pupils most often referred to agreeableness and, to a lesser degree, to extraversion and emotional stability. In Donahue's (1994) study, the most popular domain (agreeableness) was used by 73% of the subjects, whereas the least popular domain (emotional stability) was used by only 16%. On the basis of a series of five studies, Smith and Kihlstrom (1987) concluded that individuals use some of the five dimensions some of the time.…”
Section: Interviewers' Assessments Of Personalitymentioning
confidence: 99%
“…For example, one recent study found that correlations among different self-aspects (e.g., skill and interest in sports vs. quality of relationship with parents) decreased with age in a sample of French students in Grades 2 through 6 (Marsh & Ayotte, 2003). More generally, compared with younger children, adolescents are more likely to think about and describe themselves with abstract and psychological terms (e.g., "I am popular and athletic" vs. "I have a friend named Betty and I like baseball"), to differentiate among multiple aspects of the self, to recognize consistencies and inconsistencies among these self-aspects, and to organize them in a clear way (Byrne & Shavelson, 1996;Donahue, 1994;Harter, 1999Harter, , 2006Harter & Monsour, 1992;Marsh, 1989;Marsh & Ayotte, 2003;Montemayor & Eisen, 1977). By contrast, in the study of personality traits (which we review below), age trends in coherence and differentiation have received much less attention.…”
Section: Changes In Cognitive Capacities and Self-conceptmentioning
confidence: 99%
“…The continued growth of vocabulary throughout childhood and adolescence (Smith, 1941) includes the addition of new personality-relevant words, as well as increasingly frequent and complex use of such words (Donahue, 1994;Yuill, 1993). There are also changes in key reading comprehension skills (Siegler, 1998).…”
Section: Changes In Verbal Comprehensionmentioning
confidence: 99%
“…Trait self-descriptions are believed to emerge by middle childhood [Harter, 1998], but self-conceptions may become especially stable after the end of early adulthood [Roberts & Caspi, 2003], again confirming the importance of adolescence and early adulthood for development of the life story. Finally, individuals must be striving to create a coherent, continuous sense of self -and again as noted, this striving is believed to become salient in adolescence [Chandler et al, 2003;Erikson & Erikson, 1997;Harter & Monsour, 1992;Marcia, 1966], and to continue to be salient across the lifespan [Campbell, Assanand, & Di Paula, 2003;Donahue, 1994;Swann, 2000;Troll & Skaff, 1997]. The need to create both continuity and meaning via remembering the past is also posited as a special task of late life [Butler, 1963;Erikson & Erikson, 1997;Staudinger, 1989].…”
Section: Developmental Influences: Chronological Age and Self-event Rmentioning
confidence: 99%
“…Such studies suggest that the capacity to build such narratives emerges in mid-to late adolescence Habermas & Paha, 2001], and that such narratives increase in frequency throughout adulthood [Bauer & McAdams, 2004b;Pasupathi & Mansour, in press]. These findings demonstrate that the problem of personal identity emerges during adolescence [Erikson & Erikson, 1997;Harter & Monsour, 1992]; self and personality researchers have amassed data suggesting this is a problem that remains important across adulthood [Campbell, Trapnell, Heine, Katz, Lavallee, & Lehman, 1996;Donahue, 1994;Troll & Skaff, 1997]. Thus, the task of building a life story is one contoured in part by chronological age -the first sense in which personal identity and the life story are developmental problems.…”
mentioning
confidence: 99%